2013
DOI: 10.1105/tpc.113.110106
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 Regulates 1-Aminocyclopropane-1-Carboxylate Synthase Protein Turnover in Arabidopsis    

Abstract: 14-3-3 proteins are a family of conserved phospho-specific binding proteins involved in diverse physiological processes. Plants have large 14-3-3 gene families, and many binding partners have been identified, though relatively few functions have been defined. Here, we demonstrate that 14-3-3 proteins interact with multiple 1-aminocyclopropane-1-carboxylate synthase (ACS) isoforms in Arabidopsis thaliana. ACS catalyzes the generally rate-limiting step in the biosynthesis of the phytohormone ethylene. This inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 69 publications
(93 reference statements)
5
98
0
Order By: Relevance
“…hormone levels, developmental transitions). Light affects ACS stability both positively and negatively; for instance, turnover of ACS5 is decreased (Yoon and Kieber, 2013a), whereas ACS7 turnover is increased (Xiong et al, 2014) by light. Exogenous cytokinin and brassinosteroid treatments increase ethylene production via posttranslational stabilization (Woeste et al, 1999;Hansen et al, 2009), and pathogen infection increases ACS abundance at both transcriptional and posttranslational levels (Han et al, 2010;Li et al, 2012).…”
Section: Keeping Synthesis On a Short Leashmentioning
confidence: 99%
See 2 more Smart Citations
“…hormone levels, developmental transitions). Light affects ACS stability both positively and negatively; for instance, turnover of ACS5 is decreased (Yoon and Kieber, 2013a), whereas ACS7 turnover is increased (Xiong et al, 2014) by light. Exogenous cytokinin and brassinosteroid treatments increase ethylene production via posttranslational stabilization (Woeste et al, 1999;Hansen et al, 2009), and pathogen infection increases ACS abundance at both transcriptional and posttranslational levels (Han et al, 2010;Li et al, 2012).…”
Section: Keeping Synthesis On a Short Leashmentioning
confidence: 99%
“…Ethylene overproduction due to loss of ETO/EOL-mediated regulation is dramatic in etiolated seedlings but is also observed in light-grown seedlings and adult plants (Christians et al, 2009;Yoon and Kieber, 2013a).…”
Section: Phosphorylation and Proteasome-mediated Degradation: Leitmotmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have shown that the 14-3-3 proteins bind to both the ACS proteins and to the ETO1/EOL E3 ligases to regulate their stability. 14 14-3-3s generally interact specifically with phosphorylated proteins to control their function by changing their localization, activity or stability. [15][16][17][18] We demonstrated that 14-3-3 stabilizes ACS proteins via 2 distinct mechanisms.…”
mentioning
confidence: 99%
“…Consistent with this, there is a quantitative effect of disruption of the 6 copies of the ETO1/ EOL1/EOL2 genes on ethylene production in etiolated and light-grown seedlings. 10,14 If modulation of ETO1/EOL levels is a mechanism by which plants regulate ethylene biosynthesis, then the level of ETO1/EOL proteins should be regulated by a subset of factors known to regulate ethylene biosynthesis. To test this, we examined the effect of light on ETO1/EOL proteins as light has a substantial effect on ethylene biosynthesis in various plant species, including Arabidopsis.…”
mentioning
confidence: 99%